Role of Dental Professional in COVID-19 pandemic : A comprehensive review - Dr Preeti Dhir; Punia, Ramandeep Singh; Bains, Sandeep Kumar (Medico Research Chronicles, 2020)
SARS-CoV-2, a virus causing severe acute respiratory syndrome, has inundated the whole world, generating global health concerns. The World Health Organization announced that the outbreaks of the novel coronavirus have constituted a public health emergency of international concern. Transmission occurs primarily through droplet spread or contact routes. Due to the characteristics of dental settings, the risk of cross infection can be high between patients and dental practitioners. Dental specialists in the upcoming days will likely come across patients with presumed or confirmed COVID-19 and will have to ensure stringent infection prevention and control to prevent its nosocomial spread. Therefore, a greater understanding of the structure of the virus, modes of transmission, clinical features, and testing methods is needed that can help to form protocols for dental practices to identify cases and prevent further spread of infection to the patients.